Should the identified correlations between the spine, pelvis and feet be considered in the functional therapy of postural static disorders? - Marek Sokołowski; Malina Brzozowska; Bartosz Posłuszny (Kazimierz Wielki University, 2019)
The human locomotor system is a complex kinematic system whose elements remain in uninterrupted mutual subtle relations. Any changes in the position or function within the spine-pelvis complex or in lower limbs trigger mutual reactions. Therefore, one should believe that the concept of tensegration and the integrity of myofascial tapes, assuming that the normal function of the musculoskeletal system depends on the correct deployment of tension between specific elements of the system, is currently the only concept that meets the needs of the comprehensive therapy of postural mistakes and defects.